A Mixed-Methods Inquiry into the Intimate Practices of Partnered Mature Students and Influences on Relationship, Sexual, and School Satisfaction - van Rhijn, Tricia Marie; Murray, Sarah H.; Mizzi, Robert C. (Canadian Journal of Higher Education, 2015)
Through the use of mixed qualitative and quantitative methods, the current study explored the impact of postsecondary study on the intimate relationships and school experiences of partnered mature students. Quantitative regression analyses indicated that parental status, family support, partner support, and sexual desire significantly predicted relationship satisfaction, while family support and partner support significantly predicted sexual satisfaction. Age and sexual desire predicted school satisfaction for women only. Through qualitative thematic analysis it was determined that not having enough time, feeling too tired, and being stressed negatively impacted sexual satisfaction, while experiencing personal growth was described as both beneficial and problematic. Some participants reported using sex to aid in their academic success by way of offering a distraction or reducing stress. We discuss possible ways that postsecondary institutions, through their campus programs, can better address the impact school may have on mature students’ intimate relationships.